Ambicultural ambassador between East and West: Interview with Dr Ming‐Jer Chen, Leslie E. Grayson Professor, Part I. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this article is to report the first part of a recent interview with Dr Ming‐Jer Chen. He shares his values, beliefs and philosophies on life, business and scholarship, how these philosophies have shaped his approach to teaching, research and service and his strategies for making important career and professional decisions.Design/methodology/approach – This article is based on a recent interview with Dr Ming‐Jer Chen.Findings – Dr Ming‐Jer Chen's firm belief in the oneness (Fixed graphic 1 ) is reflected in his constant pursuit of "making the world smaller" by closing divides of various kinds. During his career journey, Dr Chen has applied the philosophy of "keeping a balanced and integrated view" to tackle professional and career challenges with the wisdom of an ambicultural perspective. Practices influenced by his East–West background include management education and decision‐making, as well as teaching, research and professional services.Research limitations/implications – Dr Chen's unique life and career experiences make him a role model for those who intend to pursue a career in management research. His ambicultural insight and the "balanced and integrated view" he applies may help junior scholars in dealing with challenges in their professional lives.Originality/value – The interview profiles a thought leader and strategist in management research and education, whose experience and wisdom may enlighten junior scholars along their career paths.